Penerapan Model Pembelajaran Cooverative Integrated Reading and Composition (CIRC) dalam Meningkatkan Hasil Belajar Membaca Pemahaman Siswa - Fatimah Yasmin (Universitas Cokroaminoto Palopo, 2018)
This research is classroom action research. The research aims: 1) To find out how the process of improving learning outcomes of reading comprehension by applying the CIRC model to students VI SDN 115 Pinrang. 2) To improve the results of reading comprehension learning by applying the CIRC model to students VI SDN 115 Pinrang. The research approach is a qualitative approach with the type of research is classroom action research. This study focuses on the process and student learning outcomes by implementing CIRC type cooperative learning. The subjects of this study were teachers and class V students totaling 14 people consisting of 8 men and 6 women. The design of research actions used, namely: planning, action, observation, and reflection. Data collection techniques and procedures used are observation, tests, and documentation. Furthermore, the data is analyzed and processed qualitatively. The results of the study were reading students' understanding, in the first cycle categorized as C (Enough) and in the second cycle categorized as B (Good). Conclusion The application of the CIRC model can improve the results of Indonesian language learning about reading comprehension of class students